PENGARUH KOMPOSISI BIOFERTILIZER CAIR TERHADAP PERTUMBUHAN TANAMAN KEDELAI DI LAHAN GAMBUT (The Effect of Liquid Biofertilizer Composition on Soybean Plant Growth in Peat Land): Neneng, L.1*), Jagau, Y 2), Gunawan, Y.E.1) - Administrator Journal (AgriPeat, 2018)
ABSTRACThis study aims to find the most potent combination of local microorganisms as a liquidbiofertilizer on marginal land, such as peatland. The study used Completely Randomized Design onpeat soil media in polybags, with 8 (eight) treatments and 4 (four) replicates, namely liquidbiofertilizer composition comprising a group of local microorganisms: 1) KHY, 2) IBT, 3) KHY +IBT, 4) KHY + IGT, 5) IBT + IGT, 6) KHY + IBT + IGT, 7) EM4 (Control +), 8) Aquadest(Controls -). The variables observed were plant height, number of leaves, number of branches,number of flowers of soybean crop. The results showed that the composition of the liquidbiofertilizer EM4 gave the best results on the parameters of plant height, the number of leaves, thenumber of branches, and the amount of flowers on soybean plants tested in peat soil media. Thecombined composition of local microorganisms KHY + IBT + IGT containing bacterial populationsof phosphate solvent, nitrogen-fixing bacteria, and cellulitic fungi, are still in the same group asEM4 in the treatment of the number of leaves and the number of plant flowers, therefore thecomposition of these potential local microorganisms is developed to become a liquid biofertilizerKeywords: Liquid Biofertilizer, Soybean Growth, Peat Land